The Nature of the Contract of Life Insurance Agency after Enactment of the Act Number 40 of 2014 on Insurance - HUDA, Mokhamad Khoirul; NUGRAHENI, Ninis; Kamarudin, Kamarudin (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
This research finds that the contract of the life insurance begins binding when the agent receives the premium. The principal is responsible for paying the compensation claimed by the policyholder although the insurance agent having received the premium has not deposit it into the principal’s account. If the agent is proven not to implement one of or several or all his/her obligations, the principal will punish him/her with giving verbal and/or written admonition, temporary suspension for agency-related activities or unilateral termination of the contract. If the agent is proven to break the rules i.e. to give the policyholder irrelevant or false and/or misleading information regarding to the risks, benefits, rights, and responsibility of life insurance contract, and not to transfer the submitted premium by the policyholder, he/she will be sued with maximally 5 (five) years in prison and with Rp 5.000.000.000,- (five million rupiah) as maximum fine to be paid. Thus, it is necessary to apply a good recruitment system and to select the agent who has good moral and ethics. He/she should well understand the nature of the contract of the life insurance.
Keywords: agent, principal, contract, life insurance, risk, responsibility, punishment